Organic composite material capable of photodegrading polluting gas and application
By photocuring the photocatalyst with a limit threshold structure modification on the organic carrier, a controllable organic composite material is formed, which solves the problem of low purification efficiency of existing photocatalytic technologies in confined spaces, and achieves an efficient and environmentally friendly air purification effect.
Patent Information
- Application Number
- CN202510101111.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-29
AI Technical Summary
The existing photocatalytic technology has problems such as low purification efficiency, poor gas penetration, low mass transfer and poor chemical stability when purifying indoor air, which limits its application in confined spaces.
The photocatalyst with a limit threshold structure modification is uniformly supported on the organic support by the photocuring method, forming a controllable and stable organic composite material for efficient photocatalytic purification of polluted gases.
Efficient photocatalytic purification is achieved, the air quality of the sealed room is improved, and the chemical stability and recyclability of the material avoid secondary pollution.
Smart Images

Figure CN119897167A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of air purification, and relates to a novel organic composite material, in particular to the application of photocatalytic degradation of pollutant gases in a closed indoor environment. Background Art
[0002] In recent years, with the increase of social needs, people are doing more and more work in closed indoor environments and working longer and longer in daily life, industry, military and other fields. Various pollutants released by indoor activities and building materials not only affect the indoor air quality, but also may have adverse effects on human physical and mental health. In severe cases, they may also damage the respiratory system, nervous system, etc. Therefore, improving indoor air quality has become an important issue that needs to be solved urgently.
[0003] Traditional air purification technologies include filtration, adsorption, ultraviolet disinfection, ion technology and active oxygen technology. These technologies are widely used in the field of air purification and have a broad spectrum, but they have problems such as low purification efficiency, short service life, high maintenance cost and easy secondary pollution, which limits their application in confined spaces. In contrast, photocatalytic technology has become a new indoor air purification technology with great potential due to its advantages such as high efficiency, environmental protection, durability, mild reaction conditions and no secondary pollution. This technology can be widely used in various indoor confined environments such as homes, offices, industries, and military, effectively improving indoor air quality and protecting people's health.
[0004] The photocatalytic technologies reported so far for indoor air purification mainly involve photocatalyst powders (particle size <1mm), photocatalyst particles (particle size >1mm) and photocatalytic films. Photocatalyst powders are prone to dust pollution, difficult to reuse, and have high operating costs; photocatalyst particles are large in size, and the penetration depth of light excitation is in the micrometer order, the utilization rate of surface active sites is low, mass transfer is limited, and the purification efficiency is low. Photocatalytic membranes have the advantages of high degradation efficiency, convenient operation, easy recycling, and no secondary pollution in indoor gas purification, and have great application value. For photocatalyst films prepared for gas degradation, existing studies mostly coat photocatalysts on inorganic carriers. Although the active sites of photocatalysts can be efficiently utilized to a certain extent, the catalysts are easy to fall off, the gas permeability is poor, the mass transfer driving force is low, and the photocatalytic efficiency is limited. Organic carrier photocatalytic films usually contain rich pore structures, good gas adsorption and permeability, simple preparation, good functionality, but poor chemical stability, and easy to be degraded by photocatalytic active substances. Therefore, the development and application of organic carrier photocatalytic films are still relatively limited. In view of this, there is an urgent need to develop a new type of photocatalytic organic composite material with controllable morphology, safety, stability, and simple and mild preparation conditions, so as to achieve the requirements of efficient treatment of polluted gases in closed rooms. Summary of the invention
[0005] In view of the problems and shortcomings of the prior art, the purpose of the present invention is to provide an organic composite material and application that can photodegrade polluting gases. A photocatalyst with a threshold-limited structure modification is uniformly loaded on an organic carrier by photocuring, so that it has the characteristics of controllable morphology and long-lasting stability, and is used for efficient photocatalytic purification of polluting gases.
[0006] The specific technical solution for achieving the purpose of the present invention is:
[0007] An organic composite material capable of photodegrading polluting gases, characterized by comprising the following components, by weight: 1 part of a modified photocatalyst having a threshold-limiting structure; 5-500 parts of a base material; the modified photocatalyst having a threshold-limiting structure and the base material are uniformly mixed and then formed to obtain the organic composite material capable of photodegrading polluting gases;
[0008] The base material is a mixture of resin and ethanol;
[0009] The resin is epoxy resin, epoxy acrylate, polyimide resin or acrylic resin;
[0010] The acrylic resin is polyurethane acrylic resin, polymethacrylic resin or amino acrylic resin;
[0011] The photocatalyst is TiO2, C3N4, SnO2, SrTiO3, ZnO, Fe2O3, V2O5, BiN, BiVO4, WO3, ITO or Ag3PO4;
[0012] The modification of the threshold structure includes: one or a combination of single catalyst modification, surface coating modification and interlayer composite modification;
[0013] The single catalyst modification adopts a calcination method, which specifically includes: step 1: adding a photocatalyst to a dopant solution, stirring and operating at 25-200°C for 30-120 minutes; the dopant solution is a functional group solution or a doping element solution, and the concentration is 0.1-25g / L; the functional group solution is a carboxyl, amino, sulfonic acid or hydroxyl group-containing solution; the doping element solution is a nitrogen, boron, sulfur or iron ion solution; the mass ratio of the photocatalyst to the dopant solution is 1:1-100; step 2: placing the mixture obtained in step 1 in a high-temperature furnace, calcining at 100-800°C for 1-8h, and obtaining the photocatalyst with threshold-limited structure modification after cooling;
[0014] The surface coating modification adopts a sol-gel method, specifically comprising: step 1: adding a photocatalyst to a dispersed solution, ultrasonically treating for 0.5-2 hours to obtain a mixed solution; the dispersed solution is a mixed solution of water and analytically pure cyclohexane, the volume ratio of which is 1:20-2000; the mass ratio of the photocatalyst to the dispersed solution is 1:10-100; step 2: adding the coating solution to the mixed solution prepared in step 1, stirring at 25-200°C for 2-60 hours, filtering or centrifuging, and drying at 25-200°C to obtain the coating solution; A photocatalyst modified by a limited threshold structure; wherein the coating solution is a silicon dioxide precursor solution, an aluminum oxide precursor solution or a zirconium oxide precursor solution; the silicon dioxide precursor solution includes a tetraethyl orthosilicate solution or a tetramethyl orthosilicate solution; the aluminum oxide precursor solution is an aluminum chloride solution, an aluminum nitrate solution, an aluminum sulfate solution, an aluminum carboxylate solution, an isopropoxy aluminum solution or an isopropanol aluminum solution; the zirconium oxide precursor solution includes a zirconium oxychloride solution, a zirconium acetate solution or a zirconium n-propanol solution; the mass ratio of the coating solution to the mixed solution prepared in step 1 is 1:1-100;
[0015] The interlayer composite modification adopts a modification method, which specifically includes: step 1: mixing the photocatalyst with the porous structure material, and ball milling for 1-10 hours; the porous structure material is a molecular sieve, a carbon nanotube, graphene, a metal organic framework or a covalent organic framework; the mass ratio of the photocatalyst to the porous structure material is 1-10:1-10; step 2: placing the mixed powder obtained in step 1 in a tube furnace, heat treating at 200-800°C for 2-6h, and obtaining the photocatalyst with threshold structure modification after cooling;
[0016] The modified photocatalyst with a threshold-limiting structure is uniformly mixed with a base material and then molded by a photocuring method or a 3D printing method;
[0017] The photocuring method specifically comprises: step 1: adding a photocatalyst with a threshold-limited structure modification to a base material, stirring or ultrasonically treating for 30-120 minutes, and then placing the mixture in an oven at 30-80°C for heating treatment for 5-20 minutes to obtain a mixed solution; wherein the base material is a mixed solution of resin and anhydrous ethanol, the mass ratio of which is 1-5:1-5, obtained by stirring or ultrasonically mixing for 1-100 minutes; the mass ratio of the photocatalyst to the base material is 1:5-500; step 2: irradiating the mixed solution obtained in step 1 under ultraviolet light for 0.5-10 minutes, and then drying it in a vacuum drying oven at 30-80°C for at least 6 hours to obtain the organic composite material capable of photodegrading polluting gases;
[0018] The 3D printing method specifically comprises: step 1: preparing a mixed material for 3D printing, stirring it in a light-proof condition until it is uniform; wherein the mixed material comprises a mixture of resin, photocatalyst, photoinitiator and auxiliary agent, with a mass ratio of 5-200:1-20:1-5:1; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone or 2,4,6-trimethylbenzoylphosphine oxide; the auxiliary agent is a defoamer or a rheological auxiliary agent; mixing and stirring The rotation speed is 200-400r / min, and the stirring time is 2-4h; step 2: setting a model for creating a 3D printing object in advance, and 3D printing the 3D printing mixed material obtained in step 1 to obtain the organic composite material that can photodegrade polluting gases; the 3D printing parameters are set as follows: the bottom exposure time is 15-90s, the printing exposure time is 0.5-5s, and the light-off delay is 4-6s; the printing temperature is 180-250°C; and the printing filling rate is 0.1-100%.
[0019] Furthermore, the shape of the organic composite material is square, round, diamond or irregular; the photocatalyst includes powder, block, film or sol, and also includes nanowires, nanotubes, nanospheres, nanopolygonal blocks or nano irregular shapes.
[0020] An application of the above organic composite material in photocatalytic degradation of pollutant gases under light conditions comprises the following steps:
[0021] The polluted gas is introduced into a closed light-transmitting reactor containing an organic composite material, and the reactor is irradiated with ultraviolet light or visible light. The photocatalyst in the organic composite material is excited by light and reacts with oxygen and water adsorbed on the surface to generate strong oxidizing free radicals, thereby degrading the polluted gas and achieving purification. The volume mass ratio of the gas to the organic composite material is 1-500cm 3 :1g; polluting gases include volatile organic compounds, nitrogen oxides, ammonia, hydrogen sulfide, ozone, formaldehyde or methane gas, with a concentration of 0.1-200ppm.
[0022] Furthermore, the application further comprises the following steps:
[0023] An organic composite material is directly placed in a closed space containing polluting gases. When the organic composite material is irradiated with ultraviolet light or visible light, the photocatalyst inside the organic composite material reacts with oxygen and water adsorbed on the surface to generate strong oxidizing free radicals, thereby degrading the polluting gases and achieving air purification. The closed space is an area relatively isolated from the outside world inside a car, a building, or a cabin. The organic composite material is placed directly in a place with indoor light and air flow. The light includes natural sunlight, fluorescent lamps, or ultraviolet lamps. The polluting gases include volatile organic compounds, nitrogen oxides, ammonia, hydrogen sulfide, ozone, formaldehyde, or methane gas, with a concentration of 0.1-200ppm.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses a photo-curing method to synthesize a stable organic composite material with photocatalytic odor purification function by combining a photocatalyst and an organic carrier. The synthesis process of the organic composite material is simple, the conditions are mild, and it can be completed at room temperature and pressure; secondly, the morphology of the organic composite material is controllable, the chemical properties are stable, the organic carrier is not easily degraded, it is easy to operate in practical applications, and it is convenient for recycling and treatment, and will not cause secondary pollution to the atmospheric environment; and the organic composite material has a good purification effect on the closed indoor environment, and can efficiently degrade gaseous pollutants through the combined action of adsorption and photocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a sample of the organic composite material prepared in Example 1;
[0027] Figure 2 This is a diagram showing the effect of photocatalytic degradation of H2S by the organic composite material prepared in Example 1. DETAILED DESCRIPTION
[0028] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0029] Example 1
[0030] Water and cyclohexane were mixed at a volume ratio of 1:200, TiO2 was added to the mixed solution, and ultrasonic treatment was performed for 2 hours. The mass ratio of TiO2 to the mixed solution was 1:100. Subsequently, the SiO2 precursor tetraethyl orthosilicate solution was added dropwise to the mixed suspension at a mass ratio of 1:10, stirred at 50°C for 10 hours, centrifuged, and dried at 60°C overnight to obtain a TiO2 photocatalyst with a threshold-limited structure modification.
[0031] The ethanol solution was added to the epoxy resin at a mass ratio of 1:1, and stirred for 30 minutes to prepare the base material. Then, TiO2 with a threshold structure modification was added to the base material at a mass ratio of 1:250, and ultrasonic treatment was performed for 60 minutes. The resulting mixed solution was placed in a 60°C oven for heating pretreatment for 10 minutes. An appropriate amount of the pretreatment solution was irradiated under ultraviolet light for 0.5 minutes, and dried in a 30°C vacuum drying oven for 6 hours to prepare the organic composite material sample 1 of the present invention. The prepared organic composite material is as follows Figure 1 shown.
[0032] 1 g of organic composite material sample 1 with a thickness of 1 mm is placed in a 50 cm 3 The airtight and transparent reactor was filled with polluted gas containing 30ppm hydrogen sulfide and irradiated under ultraviolet light. The timing started after the irradiation, and the concentration of hydrogen sulfide was measured by the gas detector every 5 minutes to calculate the photodegradation rate of hydrogen sulfide gas by the organic composite material. The final photocatalytic degradation efficiency of hydrogen sulfide is shown in the figure below: Figure 2 shown.
[0033] Example 2
[0034] Water and cyclohexane were mixed at a volume ratio of 1:20, C3N4 was added to the mixed solution, and ultrasonic treatment was performed for 1 hour, and the mass ratio of C3N4 to the mixed solution was 1:100. Subsequently, Al2O3 precursor aluminum chloride solution was added dropwise to the mixed suspension at a mass ratio of 1:100, stirred at 100°C for 60 hours, centrifuged, and dried at 25°C overnight to obtain a C3N4 photocatalyst with a threshold-limited structure modification.
[0035] Epoxy resin, C3N4 with threshold structure modification, 1-hydroxycyclohexyl phenyl ketone, and defoamer were stirred for 2 hours at a mass ratio of 100:10:2:1 at a speed of 200 r / min under light-proof conditions. An appropriate amount of pretreatment solution was taken as a 3D printing mixed material, and SLA technology was used to set the bottom exposure time to 20s, the printing exposure time to 4s, the light-off delay to 6s, the printing filling rate to 50%, and the printing temperature to 200°C. The organic composite material sample 2 of the present invention was obtained by printing and molding according to the set structure.
[0036] 10 g of the printed organic composite material sample 2 was directly placed in a car containing 0.1 ppm nitrogen oxide pollution gas, and light and indoor air flow were ensured.
[0037] Example 3
[0038] Water and cyclohexane were mixed at a volume ratio of 1:200, SnO2 was added to the mixed solution, and ultrasonic treatment was performed for 0.5h. The mass ratio of SnO2 to the mixed solution was 1:50. Subsequently, the ZrO2 precursor zirconium chloride solution was added dropwise to the mixed suspension at a mass ratio of 1:30, stirred at 200℃ for 5h, centrifuged, and dried at 100℃ overnight to obtain a SnO2 photocatalyst with a threshold-limited structure modification.
[0039] The ethanol solution was added to the epoxy resin at a mass ratio of 3:1, and stirred for 60 minutes to obtain a base material. Then, SnO2 with a threshold-limited structure modification was added to the base material at a mass ratio of 1:325, and stirred for 30 minutes. The resulting mixed solution was placed in a 30°C oven for heating pretreatment for 10 minutes. An appropriate amount of the pretreatment solution was taken and irradiated under ultraviolet light for 5 minutes, and dried in a 70°C vacuum drying oven for 6 hours to obtain the organic composite material sample 3 of the present invention.
[0040] 1 g of the organic composite material sample 3 with a thickness of 0.5 mm was placed in a 150 cm 3 A closed light-transmitting reactor filled with polluted gas containing 10 ppm ammonia is placed under ultraviolet light conditions.
[0041] Example 4
[0042] SrTO3 was added to 0.1 g / L amino solution and stirred at 200°C for 30 min, with the mass ratio of SrTO3 to amino solution being 1:1-100. Subsequently, it was placed in a high-temperature furnace and calcined at 300°C for 6 h, and after cooling, a SrTO3 photocatalyst with a threshold-limited structure modification was obtained.
[0043] The ethanol solution was added to epoxy acrylate at a mass ratio of 4:1, and ultrasonic treatment was performed for 45 minutes to prepare the base material. Then, SrTO3 with a threshold-limited structure modification was added to the base material at a mass ratio of 1:430, stirred for 120 minutes, and the resulting mixed solution was placed in a 30°C oven for heating pretreatment for 20 minutes. An appropriate amount of the pretreatment solution was taken and irradiated under ultraviolet light for 10 minutes, and dried in a vacuum drying oven at 80°C for 6 hours to obtain the organic composite material sample 4 of the present invention.
[0044] 20g of organic composite material sample 4 was placed directly in a 5m 3 The building is indoors and ensures light and air circulation.
[0045] Example 5
[0046] ZnO was added to a 25 g / L carboxyl solution and stirred at 500°C for 120 min, with a mass ratio of ZnO to carboxyl solution of 1:20. Subsequently, it was placed in a high-temperature furnace and calcined at 4500°C for 3 h, and after cooling, a ZnO photocatalyst with a threshold-limited structure modification was obtained.
[0047] The ethanol solution was added to the epoxy acrylate at a mass ratio of 5:1, and stirred for 30 minutes to prepare the base material. Then, the ZnO with a threshold-limited structure modification was added to the base material at a mass ratio of 1:500, and ultrasonically treated for 60 minutes. The resulting mixed solution was placed in an oven at 80°C for heating pretreatment for 5 minutes. An appropriate amount of the pretreatment solution was irradiated under ultraviolet light for 0.5 minutes, and dried in a vacuum drying oven at 30°C for 6 hours to obtain the organic composite material sample 5 of the present invention.
[0048] 1 g of organic composite material sample 5 with a thickness of 0.1 mm was placed in a 5 cm 3 A closed light-transmitting reactor filled with polluted gas containing 50 ppm ozone is placed under ultraviolet light conditions.
[0049] Example 6
[0050] Fe2O3 was added to a 10 g / L sulfonic acid solution and stirred at 25°C for 60 min, with a mass ratio of Fe2O3 to sulfonic acid solution of 1:10. Subsequently, it was placed in a high-temperature furnace and calcined at 600°C for 3 h, and after cooling, a Fe2O3 photocatalyst with a threshold-limited structure modification was obtained.
[0051] Epoxy acrylate, Fe2O3 with threshold structure modification, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and rheological additive were stirred for 4 hours at a mass ratio of 200:20:1:1 at a speed of 400r / min under light-proof conditions. An appropriate amount of pre-treatment solution was taken as a 3D printing mixed material, and DLP technology was used. The bottom exposure time was set to 60s, the printing exposure time was set to 2s, the light-off delay was set to 4s, the printing filling rate was set to 30%, and the printing temperature was set to 250°C. The organic composite material sample 6 of the present invention was obtained according to the set structure printing.
[0052] 1 g of organic composite material sample 6 with a thickness of 1 mm was placed in a 150 cm 3 A closed light-transmitting reactor filled with polluted gas containing 100 ppm formaldehyde is placed under ultraviolet light conditions.
[0053] Example 7
[0054] V2O5 was added to a 1 g / L hydroxyl solution and stirred at 55°C for 90 min, with a mass ratio of V2O5 to hydroxyl solution of 1:20. Subsequently, it was placed in a high-temperature furnace and calcined at 400°C for 2 h, and after cooling, a V2O5 photocatalyst with a threshold-limited structure modification was obtained.
[0055] The ethanol solution was added to the polyimide resin at a mass ratio of 1:3, and stirred for 60 minutes to obtain a base material. Then, V2O5 with a threshold-limited structure modification was added to the base material at a mass ratio of 1:30, and stirred for 30 minutes. The resulting mixed solution was placed in a 60°C oven for heating pretreatment for 10 minutes. An appropriate amount of the pretreatment solution was taken and irradiated under ultraviolet light for 5 minutes, and dried in a 70°C vacuum drying oven for 6 hours to obtain the organic composite material sample 7 of the present invention.
[0056] 1 g of the organic composite material sample 7 with a thickness of 2 mm was placed in a 400 cm 3 A closed light-transmitting reactor filled with polluted gas containing 150 ppm methane was placed under ultraviolet light conditions.
[0057] Example 8
[0058] TiO2 was added to a 15 g / L nitrogen source solution and stirred at 150°C for 120 min, with a mass ratio of TiO2 to the nitrogen source solution of 1:10. Subsequently, it was placed in a high-temperature furnace and calcined at 600°C for 6 h, and a TiO2 photocatalyst with a threshold-limited structure modification was obtained after cooling.
[0059] The ethanol solution was added to the polyimide resin at a mass ratio of 1:5, and stirred for 60 minutes to prepare the base material. Then, TiO2 with a threshold-limited structure modification was added to the base material at a mass ratio of 1:5, and stirred for 120 minutes. The resulting mixed solution was placed in a 30°C oven for heating pretreatment for 5 minutes. An appropriate amount of the pretreatment solution was irradiated under ultraviolet light for 10 minutes, and dried in a vacuum drying oven at 80°C for 6 hours to obtain the organic composite material sample 8 of the present invention.
[0060] 1 g of organic composite material sample 8 with a thickness of 1 mm was placed in a 500 cm 3 A closed light-transmitting reactor filled with polluted gas containing 80 ppm hydrogen sulfide is placed under ultraviolet light conditions.
[0061] Example 9
[0062] C3N4 was added to a 0.1 g / L sulfur source solution and stirred at 100°C for 30 min, with a mass ratio of C3N4 to the sulfur source solution of 1:1. Subsequently, it was placed in a high-temperature furnace and calcined at 300°C for 4 h, and after cooling, a C3N4 photocatalyst with a threshold-limited structure modification was obtained.
[0063] The ethanol solution was added to the polyimide resin at a mass ratio of 1:1, and stirred for 30 minutes to prepare the base material. Then, C3N4 with a threshold structure modification was added to the base material at a mass ratio of 1:250, and ultrasonic treatment was performed for 60 minutes. The resulting mixed solution was placed in a 30°C oven for heating pretreatment for 10 minutes. An appropriate amount of the pretreatment solution was taken and irradiated under ultraviolet light for 0.5 minutes, and dried in a 30°C vacuum drying oven for 6 hours to obtain the organic composite material sample 9 of the present invention.
[0064] 1 g of organic composite material sample 9 with a thickness of 0.25 mm was placed in a 50 cm 3 A closed light-transmitting reactor filled with polluted gas containing 30 ppm nitrogen oxides was placed under ultraviolet light conditions.
[0065] Example 10
[0066] BiN was added to a 0.5 g / L boron source solution and stirred at 80°C for 100 min. The mass ratio of C3N4 to sulfur source solution was 1:5. Subsequently, it was placed in a high-temperature furnace and calcined at 500°C for 2 h. After cooling, a BiN photocatalyst with a threshold-limited structure modification was obtained.
[0067] Polyurethane acrylic resin, BiN with threshold structure modification, 2,4,6-trimethylbenzoylphosphine oxide, and defoamer were stirred for 1.5 hours at a mass ratio of 100:2:3:1 at a speed of 250 r / min under light-proof conditions. An appropriate amount of pre-treatment solution was taken as a 3D printing mixed material, and DLP technology was used. The bottom exposure time was set to 80s, the printing exposure time was set to 3.5s, the light-off delay was set to 5.5s, the printing filling rate was set to 15%, and the printing temperature was set to 200°C. The organic composite material sample 10 of the present invention was obtained according to the set structure.
[0068] 5 g of the printed organic composite material sample 10 was directly placed in a 2 m2 chamber containing 0.1 ppm ammonia contamination gas. 3 In the cabin, and ensure light and air circulation.
[0069] Embodiment 11
[0070] BiVO4 was added to a 20 g / L iron source solution and stirred at 80°C for 30 min, with a mass ratio of BiVO4 to the iron source solution of 1:1. Subsequently, it was placed in a high-temperature furnace and calcined at 300°C for 6 h, and after cooling, a BiVO4 photocatalyst with a threshold-limited structure modification was obtained.
[0071] The ethanol solution was added to the polyurethane acrylic resin at a mass ratio of 3:1 and stirred for 60 minutes to prepare the base material. Then, BiVO4 with a threshold structure modification was added to the base material at a mass ratio of 1:325 and stirred for 30 minutes. The resulting mixed solution was placed in an oven at 80°C for heating pretreatment for 5 minutes. An appropriate amount of the pretreatment solution was irradiated under ultraviolet light for 5 minutes and dried in a vacuum drying oven at 70°C for 6 hours to obtain the organic composite material sample 11 of the present invention.
[0072] 1 g of the organic composite material sample 11 with a thickness of 0.75 mm was placed in a 150 cm 3 A closed light-transmitting reactor filled with polluted gas containing volatile organic compounds at a concentration of 10 ppm is placed under visible light conditions.
[0073] Example 12
[0074] WO3 and molecular sieve were mixed in a mass ratio of 1:1 and ball-milled for 2 hours. Subsequently, the obtained mixed powder was placed in a tube furnace and heat-treated at 200° C. for 3 hours, and after cooling, the WO3 photocatalyst with threshold-limited structure modification was obtained.
[0075] The ethanol solution was added to the polyurethane acrylic resin at a mass ratio of 4:1, and ultrasonic treatment was performed for 45 minutes to prepare the base material. Then, WO3 with a threshold-limited structure modification was added to the base material at a mass ratio of 1:430, stirred for 120 minutes, and the resulting mixed solution was placed in an oven at 80°C for heating pretreatment for 20 minutes. An appropriate amount of the pretreatment solution was taken and irradiated under ultraviolet light for 10 minutes, and dried in a vacuum drying oven at 80°C for 6 hours to obtain the organic composite material sample 12 of the present invention.
[0076] 1 g of an organic composite material sample 12 with a thickness of 0.1 mm is placed in a 200 cm 3 A closed light-transmitting reactor filled with polluted gas containing 20 ppm ozone is exposed to visible light.
[0077] Embodiment 13
[0078] ITO and carbon nanotubes were mixed in a mass ratio of 1:10 and ball-milled for 4 hours. Subsequently, the obtained mixed powder was placed in a tube furnace and heat-treated at 500° C. for 2 hours, and after cooling, the ITO photocatalyst with threshold-limited structure modification was obtained.
[0079] The ethanol solution was added to the polymethacrylic acid resin at a mass ratio of 5:1, and stirred for 30 minutes to prepare the substrate material. Then, the ITO with threshold structure modification was added to the substrate material at a mass ratio of 1:500, and ultrasonically treated for 60 minutes. The resulting mixed solution was placed in a 30°C oven for heating pretreatment for 5 minutes. An appropriate amount of the pretreatment solution was irradiated under ultraviolet light for 0.5 minutes, and dried in a 30°C vacuum drying oven for 6 hours to obtain the organic composite material sample 13 of the present invention.
[0080] 1 g of the organic composite material sample 13 with a thickness of 0.5 mm is placed in a 1 cm 3 A closed light-transmitting reactor filled with polluted gas containing 50 ppm formaldehyde was placed under visible light conditions.
[0081] Embodiment 14
[0082] Ag3PO4 and graphene were mixed in a mass ratio of 5:1 and ball-milled for 3 hours. Subsequently, the obtained mixed powder was placed in a tube furnace and heat-treated at 800° C. for 6 hours, and the Ag3PO4 photocatalyst with threshold-limited structure modification was obtained after cooling.
[0083] Polymethacrylic acid resin, Ag3PO4 with threshold structure modification, 2,4,6-trimethylbenzoylphosphine oxide, and rheological additive were stirred at a mass ratio of 50:20:5:1 at a speed of 300r / min under light-proof conditions for 3 hours. An appropriate amount of pre-treated solution was taken as a 3D printing mixed material, and SLA technology was used. The bottom exposure time was set to 30s, the printing exposure time was set to 1.5s, the light-off delay was set to 5s, the printing filling rate was set to 80%, and the printing temperature was set to 220°C. The organic composite material sample 14 of the present invention was obtained according to the set structure.
[0084] 5 g of the printed organic composite material sample 14 was directly placed in a car containing 0.1 ppm methane pollution gas, and light and air circulation were ensured.
[0085] Embodiment 15
[0086] ZnO and the metal organic framework were mixed in a mass ratio of 10:1 and ball-milled for 2 hours. Subsequently, the obtained mixed powder was placed in a tube furnace and heat-treated at 400° C. for 4 hours, and after cooling, the ZnO photocatalyst with threshold-limited structure modification was obtained.
[0087] The ethanol solution was added to the amino acrylic resin at a mass ratio of 1:3, and stirred for 60 minutes to prepare the base material. Then, the ZnO with a threshold structure modification was added to the base material at a mass ratio of 1:30, and stirred for 30 minutes. The resulting mixed solution was placed in a 60°C oven for heating pretreatment for 15 minutes. An appropriate amount of the pretreatment solution was irradiated under ultraviolet light for 5 minutes, and dried in a 70°C vacuum drying oven for 6 hours to obtain the organic composite material sample 15 of the present invention.
[0088] 1 g of an organic composite material sample 15 with a thickness of 0.5 mm is placed in a 100 cm 3 A closed light-transmitting reactor filled with polluted gas containing 150 ppm ammonia is placed under ultraviolet light conditions.
[0089] Example 16
[0090] Fe2O3 and the covalent organic framework were mixed in a mass ratio of 1:5 and ball-milled for 3 hours. Subsequently, the obtained mixed powder was placed in a tube furnace and heat-treated at 500° C. for 6 hours, and the Fe2O3 photocatalyst with threshold-limited structure modification was obtained after cooling.
[0091] The ethanol solution was added to the amino acrylic resin at a mass ratio of 1:5, and ultrasonic treatment was performed for 45 minutes to prepare the base material. Then, Fe2O3 with a threshold structure modification was added to the base material at a mass ratio of 1:5, and stirred for 120 minutes. The resulting mixed solution was placed in a 30°C oven for heating pretreatment for 20 minutes. An appropriate amount of the pretreatment solution was taken and irradiated under ultraviolet light for 10 minutes, and dried in a vacuum drying oven at 80°C for 6 hours to obtain the organic composite material sample 16 of the present invention.
[0092] 1 g of an organic composite material sample 16 with a thickness of 1 mm is placed in a 200 cm 3 A closed light-transmitting reactor filled with polluted gas containing 200 ppm hydrogen sulfide is placed under ultraviolet light conditions.
Claims
1. An organic composite material capable of photodegrading polluting gases, characterized in that: The invention is composed of the following components, in parts by weight: 1 part of a modified photocatalyst having a threshold-limiting structure; 5-500 parts of the base material; the modified photocatalyst having a threshold structure is uniformly mixed with the base material and then formed into the organic composite material capable of photodegrading polluting gases; The base material is a mixture of resin and ethanol; The resin is epoxy resin, epoxy acrylate, polyimide resin or acrylic resin; The acrylic resin is polyurethane acrylic resin, polymethacrylic resin or amino acrylic resin; The photocatalyst is TiO2, C3N4, SnO2, SrTiO3, ZnO, Fe2O3, V2O5, BiN, BiVO4, WO3, ITO or Ag3PO4; The modification of the threshold structure includes: one or a combination of single catalyst modification, surface coating modification and interlayer composite modification; The single catalyst modification adopts a calcination method, which specifically includes: step 1: adding a photocatalyst to a dopant solution, stirring and operating at 25-200°C for 30-120 min; the dopant solution is a functional group solution or a doping element solution, and the concentration is 0.1-25 g / L; the functional group solution is a carboxyl, amino, sulfonic acid or hydroxyl group-containing solution; the doping element solution is a nitrogen, boron, sulfur or iron ion solution; the mass ratio of the photocatalyst to the dopant solution is 1:1-100; step 2: placing the mixture obtained in step 1 in a high-temperature furnace, calcining at 100-800°C for 1-8 h, and obtaining the photocatalyst with threshold-limited structure modification after cooling; The surface coating modification adopts the sol-gel method, which specifically includes: step 1: adding the photocatalyst to the dispersion solution, ultrasonic treatment for 0.5-2 hours, to obtain a mixed solution; the dispersion solution is a mixed solution of water and analytical pure cyclohexane, the volume ratio is 1:20-2000; the mass ratio of the photocatalyst to the dispersion solution is 1:10-100; step 2: adding the coating solution to the mixed solution prepared in step 1, stirring the solution at 25-200°C for 2-60 minutes; h, filtering or centrifugation, and drying at 25-200° C. to obtain the photocatalyst with threshold-limited structure modification; wherein the coating solution is a silica precursor solution, an alumina precursor solution, or a zirconium oxide precursor solution; the silica precursor solution includes a tetraethyl orthosilicate solution or a tetramethyl orthosilicate solution; the alumina precursor solution is an aluminum chloride solution, an aluminum nitrate solution, an aluminum sulfate solution, an aluminum carboxylate solution, an isopropoxy aluminum solution, or an isopropanol aluminum solution; the zirconium oxide precursor solution includes a zirconium oxychloride solution, a zirconium acetate solution, or a zirconium n-propoxide solution; the mass ratio of the coating solution to the mixed solution prepared in step 1 is 1:1-100; The interlayer composite modification adopts a modification method, which specifically includes: step 1: mixing the photocatalyst with the porous structure material, and ball milling for 1-10 hours; the porous structure material is a molecular sieve, a carbon nanotube, a graphene, a metal organic framework or a covalent organic framework; the mass ratio of the photocatalyst to the porous structure material is 1-10:1-10; step 2: placing the mixed powder obtained in step 1 in a tube furnace, heat treating at 200-800°C for 2-6 hours, and obtaining the photocatalyst with threshold structure modification after cooling; The modified photocatalyst with a threshold-limiting structure is uniformly mixed with a base material and then molded by a photocuring method or a 3D printing method; The photocuring method specifically comprises: step 1: adding a photocatalyst with a threshold-limited structure modification to a base material, stirring or ultrasonically treating for 30-120 min, and then placing the mixture in an oven at 30-80°C for heating treatment for 5-20 min to obtain a mixed solution; wherein the base material is a mixed solution of resin and anhydrous ethanol, the mass ratio of which is 1-5:1-5, obtained by stirring or ultrasonically mixing for 1-100 min; the mass ratio of the photocatalyst to the base material is 1:5-500; step 2: irradiating the mixed solution obtained in step 1 under ultraviolet light for 0.5-10 min, and then drying it in a vacuum drying oven at 30-80°C for at least 6 hours to obtain the organic composite material capable of photodegrading polluting gases; The 3D printing method specifically includes: step 1: preparing a mixed material for 3D printing, and stirring it under light-proof conditions until it is uniform; wherein the mixed material includes a mixture of resin, photocatalyst, photoinitiator and auxiliary agent, and the mass ratio is 5-200:1-20:1-5:1; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone or 2,4,6-trimethylbenzoylphosphine oxide; the auxiliary agent is a defoamer or a rheological auxiliary agent; the mixing and stirring speed is 200-400 r / min, and the stirring time is 2-4 h; step 2: setting a model for creating a 3D printing object in advance, and 3D printing the 3D printing mixed material obtained in step 1 to obtain the organic composite material capable of photodegrading polluting gases; the parameters of the 3D printing are set as the bottom exposure time is 15-90 s, the printing exposure time is 0.5-5 s, and the light-off delay is 4-6 s; printing temperature is 180-250℃; printing filling rate is 0.1-100%.
2. The organic composite material according to claim 1, characterized in that: The shape of the organic composite material is square, round, diamond or irregular; the photocatalyst includes powder, block, film or sol, and also includes nanowires, nanotubes, nanospheres, nanopolygonal blocks or nano irregular shapes.
3. Use of the organic composite material according to claim 1 in photocatalytic degradation of pollutant gases under illumination conditions.
4. The use according to claim 3, characterized in that: The following steps are involved: The polluted gas is introduced into a closed light-transmitting reactor containing an organic composite material, and the reactor is irradiated with ultraviolet light or visible light. The photocatalyst in the organic composite material is excited by light and reacts with oxygen and water adsorbed on the surface to generate strong oxidizing free radicals, thereby degrading the polluted gas and achieving purification. The volume mass ratio of the gas to the organic composite material is 1-500 cm 3 ∶1g; polluting gases include volatile organic compounds, nitrogen oxides, ammonia, hydrogen sulfide, ozone, formaldehyde or methane gas, with a concentration of 0.1-200 ppm.
5. The use according to claim 3, characterized in that: The following steps are involved: An organic composite material is directly placed in a closed space containing polluting gases. When the organic composite material is irradiated with ultraviolet light or visible light, the photocatalyst inside the organic composite material reacts with oxygen and water adsorbed on the surface to generate strong oxidizing free radicals, thereby degrading the polluting gases and achieving air purification. The closed space is an area relatively isolated from the outside world in a car, a building, or a cabin. The organic composite material is placed directly in a place with indoor light and air flow. The light includes natural sunlight, fluorescent lamps, or ultraviolet lamps. The polluting gases include volatile organic compounds, nitrogen oxides, ammonia, hydrogen sulfide, ozone, formaldehyde, or methane gases, with a concentration of 0.1-200 ppm.